ENHANCING OUTDOOR BIODIVERSITY LEARNING THROUGH PERMACULTURE-BASED TEACHING MODULES - Najira, Najira; Saefudin; Taufik Rahman (DAS CONFERENCE INTERNATIONAL SERIES, 2025)
Indonesia, as a mega-biodiverse country, faces challenges in raising biodiversity awareness among students. Declining biodiversity knowledge, low vegetable consumption, and reduced interest in traditional medicinal plants highlight the need for innovative learning approaches. The COVID-19 pandemic further restricted outdoor learning. This study integrates permaculture principles into biology modules to enhance outdoor-based biodiversity learning for sustainable development. Using a qualitative experimental approach, 25 tenth-grade students from the UPI Laboratory Model Senior High School participated. The module, validated by experts, showed strong content (80%) and learning orientation (83%), with permaculture integration rated as highly relevant (90%). Implementation effectiveness reached 83%, supporting student- centered, practice-based learning. Findings emphasize permaculture’s role in fostering critical and systemic thinking in sustainability education. Challenges include outdoor classroom management and students’ unfamiliarity with scientific terms. Integrating permaculture into teaching modules proves effective for biodiversity education, aligning with Education for Sustainable Development (ESD) and Sustainable Development Goal (SDG)